2018
DOI: 10.3892/etm.2018.5687
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exposure to nicotine during pregnancy on the learning and memory for adult offspring

Abstract: We aimed to investigate the indirect influence of exposure to nicotine during pregnancy on the learning and memory of adult offspring mice. Thirty pregnant C57 mice were randomly divided into either the control group (CON) or the nicotine group (NIC), with 15 mice each. The CON group was given access to drug-free water, and the NIC group was given 60 g/ml nicotine in drinking water. Sixteen adult mice were randomly selected from the 8 litters for Morris water maze test. The level of products of related factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…9,32 Animal studies have demonstrated that prenatal nicotine exposure interferes with the formation of synapses and axons along with other neuromolecular functions resulting in problems with neurodevelopment and cognitive functioning. [28][29][30][31][32][33][34][35][36] In addition to specific neurobehavioral effects, animal research has demonstrated systemic effects of prenatal nicotine exposure on physical health resulting in increased systemic inflammation and impaired pulmonary functioning. 37,38 In addition to nicotine, prenatal e-cigarette use exposes the mother and fetus to flavoring chemicals and humectants, typically propylene glycol and vegetable glycerin.…”
Section: Discussionmentioning
confidence: 99%
“…9,32 Animal studies have demonstrated that prenatal nicotine exposure interferes with the formation of synapses and axons along with other neuromolecular functions resulting in problems with neurodevelopment and cognitive functioning. [28][29][30][31][32][33][34][35][36] In addition to specific neurobehavioral effects, animal research has demonstrated systemic effects of prenatal nicotine exposure on physical health resulting in increased systemic inflammation and impaired pulmonary functioning. 37,38 In addition to nicotine, prenatal e-cigarette use exposes the mother and fetus to flavoring chemicals and humectants, typically propylene glycol and vegetable glycerin.…”
Section: Discussionmentioning
confidence: 99%